Cell Culture Process Improvement Via Supplementation of Vitamins and Other Supplements - Bhardhwaj, Bhabya (My University, 2024)
Monoclonal antibodies have become a key class of therapeutic agents on the market and are one of the pharmaceutical industry's fastest-growing items right now. About eighty Mabs have received permission for marketing. An ever-growing need exists for the process of developing monoclonal antibodies to be optimized in a way that maximizes cost effectiveness. To do this, a thorough comprehension of the metabolic processes found in mammalian cells is required. This will facilitate the effective optimization of the chemical and physical parameters. The optimization of vitamin and other supplementation for an efficient process for producing monoclonal antibodies is described in this thesis. In this work, mammalian cell lines were used to test twelve different supplements and ten different vitamins in fed batch method. The trials were conducted in shaking flasks with identical basal media maintained at 34°C. Every day, biochemical analysis, osmo, cell count, and sampling were carried out. The shake flasks were collected and samples were tested for antibody titers using a Cedex biochemical analyzer once the cell viability dropped to 50%. Cell growth, cell viability, lactate generation, and antibody buildup in the broth were used to analyze the results. Only one additional supplement, out of ten distinct vitamins and twelve different supplements, significantly contributed to the improvements in Titer, VCC, Cell Viability, and reduced lactate buildup, while the vitamins had no discernible impact. Therefore, in the most recent round of the experiment, this additional supplement was used in certain flasks along with others that had been concentrated more. The process was optimized in this way.
Keywords: Cell culture; CHO-1; Vitamins; Amino acids; Other supplements; CHO cell line; Monoclonal antibodies